Pulsed‐Field Ablation Versus Radiofrequency Ablation for Paroxysmal Atrial Fibrillation: A Systematic Review and Meta‐Analysis - Inês Martins Esteves; Vinicius Bittar de Pontes; Thierry Trevisan; Sebastian Jaramillo; Wilton F. Gomes (Journal of Arrhythmia)
ABSTRACT Background Pulsed‐field ablation (PFA) is a nonthermal alternative to radiofrequency ablation (RFA) for patients with atrial fibrillation (AF). However, the role of PFA compared to RFA in patients with paroxysmal AF (PAF) remains unclear. Objective To compare the efficacy and safety of PFA and RFA in adult patients with PAF. Methods A systematic review and meta‐analysis were conducted following the Cochrane methodology and reported in accordance with PRISMA guidelines. The PubMed, Embase, and Cochrane databases were searched through February 2025 for studies comparing PFA and RFA in adults with PAF. The outcomes of interest included procedure time, 1‐year success rate, and major complications. All the statistical analyses were performed via R version 4.5 with a random effects model. Results One randomized controlled trial (RCT) and five observational studies comprising 3163 patients with PAF were included, of whom 972 (30.7%) underwent PFA. The follow‐up time ranged from 12 to 30 months. PFA was associated with a significantly shorter procedure time (MD –39.15 min; 95% CI –58.19 to −20.11, p < 0.01), but a significantly longer fluoroscopy time (MD 10.75 min; 95% CI 5.58–15.92, p < 0.01) as compared with RFA. There were no statistically significant differences in terms of the 1‐year success rate (RR 1.04; 95% CI 0.77–1.41, p = 0.79) and major complications (RR 0.95; 95% CI 0.60–1.52, p = 0.83) between PFA and RFA. Conclusion In this meta‐analysis, PFA was associated with a reduced operative time and an increased fluoroscopy time, with comparable 1‐year efficacy and overall safety profiles. Trial Registration PROSPERO number: CRD420251000165